Design philosophy issues of fiber reinfored polymer reinforced concrete structures - Pilakoutas, Kypros; Neocleous, Kyriacos; Guadagnini, Maurizio (My University, 2002)
The conventional design philosophy for reinforced concrete (RC) relies heavily on the ductile properties of steel. These ductile properties are used as a "fuse" and conceal the large uncertainty in the determination of modes of failure caused directly by concrete. Current design guidelines for fiber reinforced polymer (FRP) RC structures have inappropriately adopted the same design philosophy used for steel RC, leading either to the adoption of conservative safety factors or reduced structural reliability. A reliability-based analysis of FRP RC beams shows that the current, very conservative partial safety factors for FRP reinforcement on their own do not influence the structural safety of overreinforced concrete elements. Proposals are made for the modification of the material partial safety factors to achieve target safety levels.
Keywords: Concrete structures; Design; Fiber reinforced materials; Structural reliability